Digital Modeling and Display of Ancient Architecture Based on Multi-Station Laser Scanning. (October 2019) - Li, Xiaoyan; Li, Guo; Li, Pengyi; Li, Jun; Hu, Tao; Li, Meng; Yu, Ya
Abstract: In order to better display and protect ancient Chinese architecture, a three-dimensional model reconstruction method based on multi-station laser scanning is proposed. This method mainly includes several steps, such as point cloud data collection, preconditioning, multi-site cloud data fusion, point cloud data compression, 3D model reconstruction and texture mapping, environment rendering, video processing, and 3D roaming. According to the requirement of video rendering and virtual roaming, we focus on cloud processing, 3D modeling and 3D model display in this paper. Experimental results show that an famous building named Enshi Dong Drum Tower is well digitally reconstructed, so as to result in ethnic characteristics and cultural heritage protection in practical application.